A study of Islamic financial literacy in Kuala Lipis, Pahang / Nurul Azira Hmd Misbah - Hmd Misbah, Nurul Azira (Faculty of Business and Management, 2018)
Islamic financial literacy is become more important today, because it can increase level of indebtedness among people. Thus, the purpose of this research is to determine the knowledge about Islamic financial literacy and to identify the significant factor that influences Islamic financial literacy in Kuala Lipis, Pahang. A quantitative approach using a sample of 200 persons those stay in Kuala Lipis. The instrument use was self-Administered Questionnaire survey. Descriptive analysis, reliability and validity test and multiple regression analysis will be conducts using SPSS application. It is expected that view on banking product, views on Islamic banking product, parent's influence on Islamic financial product and service, factors determining investment in securities, attitude on personal financial management, influence of personal financial management, knowledge on wealth planning and management, and attitude on Islamic financial product and service have positive relationship with Islamic financial literacy.